2015
DOI: 10.1113/ep085261
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of the luteal regression: presence of progesterone receptors in coeliac ganglion

Abstract: New Findings r What is the central question of this study?The processes involved in luteal involution have not yet been clarified and, in general, have been studied only from a hormonal point of view. We investigated whether progesterone, from the coeliac ganglion through the superior ovarian nerve, is able to modify the luteal regression of late pregnancy in the rat. r What is the main finding and its importance?We showed that the luteal regression might be reversed by the neural effect of progesterone and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Besides, according to a relevant research, the inhibition of NF‐κB signaling pathway increased the anti‐apoptotic factor Bcl‐2 and decreased the pro‐apoptotic factors Bax and Fasl (Mattson, ). Bcl‐2, Bax, and Fasl were apoptosis‐related proteins, and their expressions influenced cell apoptosis (Ghersa et al, ). To further verify this role of the inhibition of NF‐κB signaling pathway, the present study analyzed the effect of this pathway on these apoptosis‐related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, according to a relevant research, the inhibition of NF‐κB signaling pathway increased the anti‐apoptotic factor Bcl‐2 and decreased the pro‐apoptotic factors Bax and Fasl (Mattson, ). Bcl‐2, Bax, and Fasl were apoptosis‐related proteins, and their expressions influenced cell apoptosis (Ghersa et al, ). To further verify this role of the inhibition of NF‐κB signaling pathway, the present study analyzed the effect of this pathway on these apoptosis‐related factors.…”
Section: Discussionmentioning
confidence: 99%
“…80 In the present study, SMG incubation with ALLO had an anti-apoptotic effect, significantly decreasing FAS-L ovarian mRNA expression. These results are similar to the reported effects of progesterone administration to an ex vivo CG-SON-ovary system, 84 where the treatment induced an anti-apoptotic effect through FAS-L decrease without changes in the BAX/BCL-2 ratio. ALLO thus may be involved in a part of progesterone actions because it has been suggested that some effects of progesterone might be mediated by active metabolites.…”
Section: Discussionsupporting
confidence: 90%